2011
DOI: 10.1371/journal.pone.0016727
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Activity Modulates Alternative Splicing

Abstract: There is increasing evidence to suggest that splicing decisions are largely made when the nascent RNA is still associated with chromatin. Here we demonstrate that activity of histone deacetylases (HDACs) influences splice site selection. Using splicing-sensitive microarrays, we identified ∼700 genes whose splicing was altered after HDAC inhibition. We provided evidence that HDAC inhibition induced histone H4 acetylation and increased RNA Polymerase II (Pol II) processivity along an alternatively spliced elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
138
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(150 citation statements)
references
References 55 publications
(82 reference statements)
9
138
0
1
Order By: Relevance
“…For example, when HeLa cells were treated with sodium butyrate, a pan-HDAC inhibitor, close to 700 alternative exons changed their splicing patterns. 28 This study further implicated, using ChIP analysis, that the treatment induced histone H4 hyperacetylation, and increased RNAPII processivity, inferred from reduced RNAPII association, across chromatin regions containing alternative exons, although a direct measurement of transcriptional elongation rate was not conducted. 28 In another study using depolarized neuronal cells, it was suggested that increased skipping of exon 18 in the NCAM premRNA was correlated with a localized increase of H3K9 acetylation and H3K36 trimethylation, as well as increased local RNAPII movement.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For example, when HeLa cells were treated with sodium butyrate, a pan-HDAC inhibitor, close to 700 alternative exons changed their splicing patterns. 28 This study further implicated, using ChIP analysis, that the treatment induced histone H4 hyperacetylation, and increased RNAPII processivity, inferred from reduced RNAPII association, across chromatin regions containing alternative exons, although a direct measurement of transcriptional elongation rate was not conducted. 28 In another study using depolarized neuronal cells, it was suggested that increased skipping of exon 18 in the NCAM premRNA was correlated with a localized increase of H3K9 acetylation and H3K36 trimethylation, as well as increased local RNAPII movement.…”
Section: Discussionmentioning
confidence: 83%
“…28 This study further implicated, using ChIP analysis, that the treatment induced histone H4 hyperacetylation, and increased RNAPII processivity, inferred from reduced RNAPII association, across chromatin regions containing alternative exons, although a direct measurement of transcriptional elongation rate was not conducted. 28 In another study using depolarized neuronal cells, it was suggested that increased skipping of exon 18 in the NCAM premRNA was correlated with a localized increase of H3K9 acetylation and H3K36 trimethylation, as well as increased local RNAPII movement. 21 A previous study from our own laboratory also provided a link between localized histone hyperacetylation and exon skipping, although in this case, the histone hyperacetylation depends on a splicing regulator.…”
Section: Discussionmentioning
confidence: 83%
“…An in vitro study of mammalian cells showed that DNA methylation inhibited the binding of transcription factor CCCTC binding factor (CTCF), which affected alternative splicing (14). Regulation of AS is a complicated process that also involves spliceosome assembly (7,15), chromatin structure (16,17), siRNA activity (18), and transcriptional elongation (19), in addition to the apparent action of methylation.…”
mentioning
confidence: 99%
“…An example is the histone acetyltransferase Gcn5, which is a member of the yeast SAGA complex involved in cotranscriptional recruitment of the U2 snRNP (39). Similarly, the SWI/SNF chromatin-remodeling complex in higher eukaryotes associates with pre-mRNA and regulates alternative splicing of endogenous genes (40), and treatment with the histone deacetylase inhibitor sodium butyrate (NaB) and loss of HDAC1 affect alternative splicing (41).…”
Section: Bs69 Suppresses Transcription Elongation and Promotes Intronmentioning
confidence: 99%